Allogeneic vs. autologous intra‐articular mesenchymal stem cell injection within normal horses: Clinical and cytological comparisons suggest safety. (24th June 2019) - Colbath, A. C.; Dow, S. W.; Hopkins, L. S.; Phillips, J. N.; McIlwraith, C. W.; Goodrich, L. R.
Summary: Background: Allogeneic bone marrow‐derived mesenchymal stem cells (BMDMSCs) could provide multiple advantages over autologous BMDMSCs, including creating an 'off‐the‐shelf' treatment together with the ability to control for donor variation. Objectives: The objective of the study was to compare the clinical and synovial fluid response of the normal equine joint to autologous and pooled‐allogeneic BMDMSCs while controlling for individual variation and joint variations in response to intra‐articular injections. We hypothesised that, by controlling for individual animal and joint variation, we could identify differences between allogeneic vs. autologous BMDMSCs in noninflamed joints. Study design: Randomised‐controlled experiment. Methods: Bone marrow was harvested from eight horses. Autologous BMDMSCs were culture expanded, cryopreserved and thawed immediately prior to administration. For allogeneic BMDMSC treatments, four horses' BMDMSCs were culture expanded, pooled, cryopreserved and thawed immediately prior to use. Ten million (autologous or pooled‐allogeneic) BMDMSCs were administered into contralateral forelimb metacarpophalangeal joints so that every autologous and allogeneic injection could be compared within the same animal. Clinical parameters included subjective lameness, objective lameness (Lameness Locator™), response to flexion, joint circumference and joint effusion. Arthrocentesis was performed for assessment of the nucleated cell count, differential cell count, total protein, and synovial concentrations of prostaglandin E2 (PGE2) and c‐reactive protein (CRP). All parameters were measured at baseline, 6, 12, 24, 72, 168 and 336 h post‐injection. Results: No difference was detected in any parameters between forelimb metacarpophalangeal joints administered autologous or pooled‐allogeneic BMDMSCs. Main limitations: This study did not attempt to measure efficacy of BMDMSCs for musculoskeletal disease and should be followed by properly controlled efficacy trials. Conclusions: The study did not identify any clinical or cytological differences in the normal joint response to allogeneic or autologous BMDMSCs. A larger study to prove equivalence is warranted as allogeneic BMDMSCs may be a feasible alternative to autologous BMDMSCs.